О надгробии Гая Юлия Валента из Херсонеса - Цукерман, К. (Материалы по археологии, истории и этнографии Таврии, 2003)
В 1996 г. Е.Я.Туровский и А.А.Филиппенко опубликовали воинское надгробие с латинской эпитафией, поступившее за год до того в Национальный заповедник “Херсонес Таврический” (г. Севастополь) и найденное, по-видимому, на нераскопанном участке городского некрополя. Авторы отмечают, что могильная плита (ширина - 0,73 м, толщина -0,17 м, сохранившаяся высота -1,1 м) является на настоящий момент самым крупным римским надгробием из Херсонеса и его округи. The gravestone of Gaius Julius Valens, a soldier in the cohors I Sugambrorum veterana, was recently acquired by the State Museum of Chersonesus Taurica (Sebastopol). It seems to originate from the unexplored part of the city necropolis and be the largest funeral monument of a Roman soldier found in Crimea. The Latin epitaph is slightly mutilated. Its reading and restoration are debated in two successive publications of the monument (Turovskij, Filippenko 1996: see above the text on the left; Zubar’, Son 1997 and 2000: the text on the right) which both fail to produce a coherent text. The stumbling block in both cases is the unusual form aeres, interpreted as an irregular plural of aes (pi. aera). Once, however, this form is identified as a phonetic spelling of heres, heir, and the reading of one letter (1.6) is revised on the photograph (in Turovskij, Filippenko 1996), the epitaph becomes coherent (as printed above) and the monument can be recognized as the work of Valens’ freedman and heir for his former master, now patronus.